PELINDIAN REDUKTIF BIJIH MANGAN NUSA TENGGARA TIMUR DENGAN MENGGUNAKAN MOLASES DALAM SUASANA ASAM[Reductive Leaching of Manganese Ore from East Nusa Tenggara With Molasses in Sulfuric Acid Solution] - Sumardi, Slamet; Mubarok, Mohammad Zaki; Saleh, Nuryadi; Firdiyono, F (Jurnal Metalurgi, 2012)
Manganese is the fourth most used metal in daily lives besides iron, aluminium and copper. Other usage of manganese is for chemical raw material disinfectant and chemical oxidizing. This experiment was done in Kupang, East Nusa Tenggara to extract manganese from manganese ores by reductive leaching in sulfuric acid conditions. Molasses as waste from sugarcane factory is used as redactor. The purpose of this experiment is to measure the impact of sulfuric acid concentration, leaching temperature and solid percentage on percentage of manganese extraction and percentage of iron solubility extraction. This experiment is preparing manganese ores by reducing into 140 mesh and analyze ores compositions using XRF. Some amounts of manganese ores are inserting into leaching reactor which contains sulfuric acid and molasses. Variables in this experiment are leaching concentration (sulfuric acid), leaching temperature and solid percentage. This leaching is reductive in 6 hours with constant speed 200 rpm. Leaching solution is filtered to separate filtrate with from obtained residue. Filtrate is analyzed using AAS to measure manganese and iron content. Meanwhile residue is dried and weighed. We conclude that manganese extraction on manganese ores from Kupang, NTT can be carried by reductive leaching using molasses as reductive agent on sulfuric acid media. The highest manganese extraction for this experiment is 95, 33 % which can be achieved by using 6% sulfuric acid, 70 oC temperature, 10 % solid, 100 g/L molasses,200 rpm mixing speed and 6 hours of leaching .